Renewable electric energy integration: Quantifying the value of design of markets for international transmission capacity - Karsten Neuhoff; Rodney Boyd; Thilo Grau; Julian Barquin; Francisco Echavarren; Janusz Bialek; Chris Dent; Christian von Hirschhausen; Benjamin Hobbs; Friedrich Kunz; Hannes Weigt; Christian Nabe; et al. (Deutsches Institut für Wirtschaftsforschung (DIW), 2011)
Integrating large quantities of supply-driven renewable electricity generation remains a political and operational challenge. One of the main obstacles in Europe to installing at least 200 GWs of power from variable renewable sources is how to deal with the insufficient network capacity and the congestion that will result from new flow patterns. We model the current methodology for controlling congestion at international borders and compare its results, under varying penetrations of wind power, with a model that simulates an integrated European network that utilises nodal/localised marginal pricing. The nodal pricing simulations illustrate that congestion - and price - patterns vary considerably between wind scenarios and within countries, and that a nodal price regime could make fuller use of existing EU network capacity, introducing substantial operational cost savings and reducing marginal power prices in the majority of European countries.
Keywords: 330; Power market design; renewable power integration; congestion management; transmission economics